Social Dynamics in a Systems Perspective (New Economic Windows,, 2018)
This book targets the critical issue of decision making in uncertain conditions and situations. The aim is to increase readers' understanding of complexity and of socio-economic interactions through the application of systems thinking perspectives. Among the various areas and topics addressed are complexity and sustainable management, markets as complex adaptive systems, the impacts of psychological and emotional factors upon value co-creation exchanges, and ICT enablers of service network performance and service exchange fulfillment. Thanks to the chosen perspectives, all of which are based on different systems research streams, the book will support more consistent and robust decisions, leading to sustainable, wise, and viable systems dynamics. It will aid managers, practitioners, and consultants in their decision-making processes and will also be of interest for academics and scholars in management, systems, computer science, engineering, and marketing.